1974
DOI: 10.1172/jci107592
|View full text |Cite
|
Sign up to set email alerts
|

Role of the pituitary and thyroid glands in the decline of minimal O2 consumption with age.

Abstract: A B S T R A C T Resting 02 consumption rate (BMR) or minimal 02 consumption rate (MOC) declines with age. Data are presented that suggest that a newly described function of the pituitary may be responsible for a considerable part of the total 75% decline in the MOC with age. The new function appears to decrease the responsiveness of peripheral tissues to thyroid hormones. Response curves to injected thyroxine indicated that immature rats were three times more responsive to thyroxine than adult rats. All the ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
35
0
3

Year Published

1975
1975
2015
2015

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 105 publications
(39 citation statements)
references
References 25 publications
1
35
0
3
Order By: Relevance
“…Although several age-related changes have been re ported to be thyroid hormone dependent [4,7], this report implicates the central nervous system in this regard. Numer ous studies have shown that the central nervous system is markedly dependent on thyroid hormones for its overall growth and its morphological and biochemical develop ment [5,14).…”
Section: Discussionmentioning
confidence: 53%
See 1 more Smart Citation
“…Although several age-related changes have been re ported to be thyroid hormone dependent [4,7], this report implicates the central nervous system in this regard. Numer ous studies have shown that the central nervous system is markedly dependent on thyroid hormones for its overall growth and its morphological and biochemical develop ment [5,14).…”
Section: Discussionmentioning
confidence: 53%
“…With increasing age, in the rat there is a thyroid hormone-dependent decline in mini mal oxygen consumption (MOC) [4], and studies in humans show a decline in thyroxine (T4) secretion [7] and the abso lute rate of thyroid iodine accumulation [8], Data also sug gests an age-related insensitivity to thyroid hormone at the tissue level [4,11] and a thyroid hormone-dependent decline in rat renal cortical Na*-K+ ATPase [11]. Much work has been done to evaluate serum T3 concentrations in respect to increasing age [12,15,22).…”
mentioning
confidence: 99%
“…Similar increases in lysosomal enzyme activities also occurred when physiologic doses of T3 (2 jg/100 g body wt per day) were injected into hypophysectomized rats (Table 4). This dose caused a small but significant increase in body weight and should be equivalent to the amount normally produced by rats of this size (23).…”
Section: Resultsmentioning
confidence: 96%
“…Although the exact reason for the disparity is not clear at present, the difference in the experimental settings may be one of the major sources of the disparity. It should be noted that the respiratory activity differs depending on the age of animals [19], the constituents of incubation medium, respiratory substrates, and the presence or absence of ADP and the ATP-trapping system (hexokinase plus glucose). Similarly, the phosphorylation efficiency has been reported either increased [I21 or decreased [9, 141. In the present study, liver mitochondria from hypothyroid rats were shown to exhibit a normal activity in succinate dehydrogenase and a near normal activity in the succinoxidase system.…”
Section: Resultsmentioning
confidence: 99%